Rethinking design and interiors human beings in the built environment - Caan, Shashi (London Laurence King Publishing, 2011)
"Rethinking Design and Interiors explores the position of design in relation to our complex and ever-changing world and promotes a deeper knowledge - with input from the arts sciences, and technology - that will support design's integral role in the advancement of humankind in the twenty-first century."--From back cover.
Preface / Susan S. Szenasy -- Introduction -- The search for shelter: Shelter's human roots; The lost origins of building; Reclaiming the past -- Being: Interior space and the second skin; Extensions of self; The un-universal man; Design for basic human needs (measures of man); Design for well-being -- Inside: The emergence of prevailing sterotypes; The psychology analogy; Empirical knowledge; Designing habitable space -- Design: Toward a new design; Acknowledging design's complex nature; The development of experiential knowledge; Establishing a protocol for phenomenological investigations; The identfication of qualitative design factors -- Epilogue: out from within.
Includes bibliographical references (pages 193-197) and index.
Keywords: Interior architecture; Architectural design -- History; Architecture, Modern